The Effects of Infertility on the Quality of Life of Women: A Comparative Study in a Nigerian Tertiary Centre - Lucky Amadi; Farouk Oladeji Raji; Oluwaseyi Isaiah Odelola (Nigerian Journal of Medicine)
Background: Infertility can be difficult for couples. This study investigated the effect of infertility on women’s quality of life (QoL), by comparing women with infertility and fertile women attending a tertiary health centre in Ogun State, Nigeria. Materials and Methods: This study involved 84 women with infertility and 168 fertile women receiving obstetrics and/or gynaecological care at Olabisi Onabanjo University Teaching Hospital. Their QoL was compared using the World Health Organization QoL -BREF questionnaire. Continuous and categorical variables were summarised, and Student’s t-test and Chi-square test were used to perform comparison and association analyses. Results: In the psychological, social and overall QoL, fertile women scored higher (better QoL) (t = −3.111, P = 0.00; t = −3.667, P = 0.001; t = −2.550, P = 0.011, respectively). Women with secondary infertility had better QoL in the social domain (t = −2.299, P = 0.024). In addition, the women’s QoL was significantly related to their age, level of education and that of their spouses, spousal employment status and the duration of marriage (P < 0.05). Conclusion: Infertile women often experience a lower QoL, and this should be considered in the care given to women with fertility issues.